Impact of Lockdown due to COVID-19 on lifestyle and diet pattern of college students of Eastern India: A cross-sectional survey - Nirala, Santosh Kumar; Naik, Bijaya; Rao, Rajath; Pandey, Sanjay; Singh, Chandramani; Chaudhary, Neha (Nepal Journal of Epidemiology, 2022)
Background: The emergence of the COVID-19 pandemic and lockdown measures to confine it has disrupted the routine of the public. The impact of such long-term confinements on the lifestyle and diet of students are not known and hence this study was designed to assess the impact of lockdown due to the COVID-19 pandemic on the lifestyle and diet of university students. Methods: An online cross-sectional survey among 622 university students across various educational institutes of east India using a pre-designed questionnaire about lifestyle-diet before and during the lockdown. Results were tabulated and statistical tests like Paired t-test, Wilcoxon Rank sign test, and Mc-Nemar tests were applied and overall significance was attributed to P<0.05. Results: During the lockdown a total of 2.4% (95% CI: 1.4-3.8%) decrease in prevalence of tobacco use, 8.7% (95% CI: 6.6-11%) decrease in physical activity and a 0.8 hour (95% CI: 0.6-0.9 hour) increase in the mean sleep duration was observed. There was a significant increase in use of fresh fruits consumption [Median(IQR)-before:2(1-5);during:3(1-5) days] and a decrease in meat-poultry[Median(IQR)-before: 2(0-3);during: 1(0-3)days] and junk food[Median(IQR)-before:1(0-2);during:0(0-2)days] consumption during the lockdown. Conclusion: A significant proportion of changes in lifestyle and frequency of consumption of certain food items in the dietary pattern during the lockdown.